Compact anti-crack fused zirconia corundum brick and preparation method thereof
By optimizing the formulation and process of electromelted zirconium corundum bricks, a dense crack resistance electromel corundum brick is formed, which solves the problems of insufficient crack resistance and limited service life in the existing technology, and achieves higher high temperature resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411759764.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing electromelted zirconium corundum bricks have insufficient crack resistance in actual applications and have limited service life, making it difficult to meet the demand for refractory materials in high-temperature industries.
By optimizing the formulation, including the composition ratios of alumina, zirconium dioxide, silica, niobium pentoxide, soda ash, manganese dioxide and copper oxide, and using process measures such as particle size ratio and oxygen blowing treatment, a dense tissue structure is formed, reducing the appearance of pores and improving crack resistance.
It significantly improves the density and crack resistance of electromelted zirconium corundum bricks, extends its service life, enhances its high temperature resistance, corrosion resistance and thermal shock resistance, and reduces the operation and maintenance costs of glass kilns.
Smart Images

Figure BDA0005167316760000111 
Figure BDA0005167316760000112 
Figure BDA0005167316760000121
Abstract
Description
Technical Field
[0001] The invention relates to a dense crack-resistant fused zirconium corundum brick and a preparation method thereof, belonging to the technical field of refractory materials. Background Art
[0002] With the development of the glass industry, the requirements for refractory materials are getting higher and higher. Traditional refractory materials such as silica bricks are no longer suitable when the temperature in the kiln exceeds 1600℃. In recent years, fused zirconium corundum bricks have developed rapidly. They can withstand high temperatures of more than 1700℃ and are light in weight. They are one of the important refractory materials in modern glass melting furnaces and are usually used in the most critical parts of glass furnaces. At present, domestic and foreign manufacturers have launched fused zirconium corundum bricks with different zirconium contents.
[0003] Although fused zirconium corundum bricks have many advantages, there are still some problems in practical applications, such as insufficient crack resistance and limited service life. It is necessary to further improve the density and crack resistance of fused zirconium corundum bricks to meet the demand for refractory materials in the glass industry and other high-temperature industries, and increase the market competitiveness and economic benefits of enterprises. Summary of the invention
[0004] Aiming at at least one problem existing in the above-mentioned prior art, the present invention provides a dense and crack-resistant fused zirconium corundum brick, which has excellent density and crack resistance and greatly prolongs its service life; and also provides a preparation method thereof.
[0005] In order to achieve the above-mentioned object, the present invention adopts the following technical scheme: a dense crack-resistant fused zirconium corundum brick, comprising the following raw materials, calculated by mass fraction: 42.7-46.6% alumina, 36.8-40.5% zirconium dioxide, 11.5-14.2% silicon dioxide, 2.5-4.4% niobium pentoxide, 0.7-1.1% soda ash, 0.6-1% manganese dioxide and 0.5-1% copper oxide;
[0006] The aluminum dioxide is composed of aluminum dioxide with a particle size of 200 to 300 nm and a particle size of 25 to 50 μm;
[0007] The zirconium dioxide is composed of zirconium dioxide with a particle size of 50 to 100 nm and a particle size of 50 to 100 μm;
[0008] The particle size of the silicon dioxide is 100-200 nm.
[0009] Preferably, in aluminum dioxide, the mass fraction of aluminum dioxide with a particle size of 25-50 μm accounts for 25-30% of the mass fraction of aluminum dioxide with a particle size of 200-300 nm, and in zirconium dioxide, the mass fraction of zirconium dioxide with a particle size of 50-100 μm accounts for 20-25% of the mass fraction of zirconium dioxide with a particle size of 50-100 nm.
[0010] Preferably, the dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 44.5% alumina, 38.1% zirconium dioxide, 12.2% silicon dioxide, 3.1% niobium pentoxide, 0.9% soda ash, 0.7% manganese dioxide and 0.6% copper oxide.
[0011] Preferably, in aluminum dioxide: the mass fraction of aluminum dioxide with a particle size of 25-50 μm accounts for 28.2% of the aluminum dioxide with a particle size of 200-300 nm; and in zirconium dioxide: the mass fraction of zirconium dioxide with a particle size of 50-100 μm accounts for 22.5% of the zirconium dioxide with a particle size of 50-100 nm.
[0012] The present invention also provides a method for preparing a dense crack-resistant fused zirconium corundum brick, comprising the following steps:
[0013] (1) grinding alumina, zirconium dioxide and silicon dioxide to a desired particle size, and then uniformly mixing with soda ash, niobium pentoxide, manganese dioxide and copper oxide to obtain a mixture;
[0014] (2) pouring the above-mentioned mixed material into an electric arc furnace, melting it into a molten liquid at a temperature of 1890-1910° C., and then continuing to heat it to 2730-2750° C., then keeping it warm and blowing oxygen to remove carbon and oxidize the liquid to obtain a molten liquid;
[0015] (3) The above molten material is cast in a specially designed product mold, and annealed and cooled in stages at different cooling rates to obtain dense, crack-resistant fused zirconium corundum bricks.
[0016] Preferably, the time for heat preservation and oxygen blowing treatment in step (2) is 20 to 25 minutes.
[0017] Preferably, during casting in step (3), the temperature of the molten liquid is between 2600 and 2650°C.
[0018] Preferably, in step (3), annealing and cooling are performed in stages at different cooling rates: the annealing starting temperature is 2020-2100° C., first cooled to 1350-1420° C. at a rate of 20-30° C. / h, then cooled to 950-1015° C. at a rate of 40-50° C. / h, and then cooled to 410-460° C. at a rate of 20-30° C. / h, and then naturally cooled.
[0019] Preferably, the annealing starting temperature is 2020-2100° C. and is kept at this temperature for 90-120 min, and then the temperature is lowered to 1350-1420° C. and is kept at this temperature for 60-90 min.
[0020] Beneficial effects of the present invention: the fused zirconium corundum bricks of the present invention have excellent density and crack resistance, and can significantly extend the service life of refractory materials; the fused zirconium corundum bricks of the present invention promote the uniform density of the organizational layers between alumina, zirconium dioxide and silicon dioxide by adding niobium pentoxide, manganese dioxide and copper oxide, greatly reduce the appearance of pores, can further delay the generation and expansion of cracks, and improve its high temperature resistance, corrosion resistance and thermal shock resistance, thereby reducing the operation, maintenance and renewal costs of glass kilns, and improving the economic benefits of enterprises; the preparation method of the fused zirconium corundum bricks of the present invention has a simple process and appropriate parameter design, and can obtain dense and crack-resistant fused zirconium corundum bricks with good product quality. DETAILED DESCRIPTION
[0021] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.
[0022] The purity of the soda ash in the present invention is not less than 99.5%; the purity of zirconium dioxide is not less than 99.5%; the purity of aluminum dioxide is not less than 99.0%; and the purity of silicon dioxide is between 98% and 99%.
[0023] Example 1
[0024] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 35.04% of aluminum oxide with a particle size of 200-300nm, 8.76% of aluminum oxide with a particle size of 25-50μm, 26.25% of zirconium dioxide with a particle size of 50-100nm, 11.25% of zirconium dioxide with a particle size of 50-100μm, 11.5% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide, 0.8% of soda ash, 0.7% of manganese dioxide and 0.6% of copper oxide;
[0025] The specific process of its preparation method is as follows:
[0026] (1) grinding alumina, zirconium dioxide and silicon dioxide to a desired particle size, and then uniformly mixing with soda ash, niobium pentoxide, manganese dioxide and copper oxide to obtain a mixture;
[0027] (2) pouring the above-mentioned mixed material into an electric arc furnace, melting it into a molten liquid at a temperature of 1890-1910° C., and then continuing to heat it to 2730° C., and then keeping it at that temperature for 25 minutes while blowing oxygen to remove carbon and oxidize the liquid material to obtain a molten liquid material;
[0028] (3) In a specially designed product mold, the above molten material with a casting temperature of 2650°C is cast to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2050°C, and it is kept at this temperature for 110 minutes, then cooled to 1370°C at a rate of 20-30°C / h, and kept at this temperature for 85 minutes, then cooled to 1015°C at a rate of 40-50°C / h, and then cooled to 460°C at a rate of 20-30°C / h, and then naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0029] Example 2
[0030] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 30.29% of aluminum oxide with a particle size of 200-300nm, 16.31% of aluminum oxide with a particle size of 25-50μm, 31.45% of zirconium dioxide with a particle size of 50-100nm, 5.55% of zirconium dioxide with a particle size of 50-100μm, 11.7% of silicon dioxide with a particle size of 100-200nm, 2.6% of niobium pentoxide, 0.8% of soda ash, 0.7% of manganese dioxide and 0.6% of copper oxide;
[0031] The specific process of its preparation method is exactly the same as that of Example 1.
[0032] Example 3
[0033] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 17.08% of aluminum oxide with a particle size of 200-300nm, 25.62% of aluminum oxide with a particle size of 25-50μm, 16.2% of zirconium dioxide with a particle size of 50-100nm, 24.3% of zirconium dioxide with a particle size of 50-100μm, 12.5% of silicon dioxide with a particle size of 100-200nm, 2.5% of niobium pentoxide, 0.7% of soda ash, 0.6% of manganese dioxide and 0.5% of copper oxide;
[0034] The specific process of its preparation method is exactly the same as that of Example 1.
[0035] Example 4
[0036] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 29.89% of aluminum oxide with a particle size of 200-300nm, 12.81% of aluminum oxide with a particle size of 25-50μm, 31.59% of zirconium dioxide with a particle size of 50-100nm, 8.91% of zirconium dioxide with a particle size of 50-100μm, 12.5% of silicon dioxide with a particle size of 100-200nm, 2.5% of niobium pentoxide, 0.7% of soda ash, 0.6% of manganese dioxide and 0.5% of copper oxide;
[0037] The specific process of its preparation method is exactly the same as that of Example 1.
[0038] Example 5
[0039] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.39% of aluminum oxide with a particle size of 200-300nm, 11.61% of aluminum oxide with a particle size of 25-50μm, 27.6% of zirconium dioxide with a particle size of 50-100nm, 9.2% of zirconium dioxide with a particle size of 50-100μm, 14.2% of silicon dioxide with a particle size of 100-200nm, 3.2% of niobium pentoxide, 1.1% of soda ash, 0.9% of manganese dioxide and 0.8% of copper oxide;
[0040] The specific process of its preparation method is exactly the same as that of Example 1.
[0041] Example 6
[0042] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 32.85% of aluminum oxide with a particle size of 200-300nm, 10.95% of aluminum oxide with a particle size of 25-50μm, 30% of zirconium dioxide with a particle size of 50-100nm, 7.5% of zirconium dioxide with a particle size of 50-100μm, 11.5% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide, 0.8% of soda ash, 1% of manganese dioxide and 1% of copper oxide;
[0043] The specific process of its preparation method is as follows:
[0044] (1) grinding alumina, zirconium dioxide and silicon dioxide to a desired particle size, and then uniformly mixing with soda ash, niobium pentoxide, manganese dioxide and copper oxide to obtain a mixture;
[0045] (2) pouring the above-mentioned mixed material into an electric arc furnace, melting it into a molten liquid at a temperature of 1890-1910° C., and then continuing to heat it to 2740° C., and then keeping it at that temperature for 22 minutes while blowing oxygen to remove carbon and oxidize the liquid material to obtain a molten liquid material;
[0046] (3) In a specially designed product mold, the casting temperature of the above molten liquid is maintained at 2630°C to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2100°C, and it is kept at this temperature for 90 minutes, then cooled to 1350°C at a rate of 20-30°C / h, and kept at this temperature for 90 minutes, then cooled to 950°C at a rate of 40-50°C / h, and then cooled to 410°C at a rate of 20-30°C / h, and then naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0047] Example 7
[0048] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 33.552% of aluminum oxide with a particle size of 200-300nm, 13.048% of aluminum oxide with a particle size of 25-50μm, 28.86% of zirconium dioxide with a particle size of 50-100nm, 8.14% of zirconium dioxide with a particle size of 50-100μm, 11.7% of silicon dioxide with a particle size of 100-200nm, 2.6% of niobium pentoxide, 0.8% of soda ash, 0.7% of manganese dioxide and 0.6% of copper oxide;
[0049] The specific process of its preparation method is as follows:
[0050] (1) grinding alumina, zirconium dioxide and silicon dioxide to a desired particle size, and then uniformly mixing with soda ash, niobium pentoxide, manganese dioxide and copper oxide to obtain a mixture;
[0051] (2) pouring the above-mentioned mixed material into an electric arc furnace, melting it into a molten liquid at a temperature of 1890-1910° C., and then continuing to heat it to 2750° C., and then keeping it at this temperature for 20 minutes while blowing oxygen to remove carbon and oxidize the liquid material to obtain a molten liquid material;
[0052] (3) In a specially designed product mold, the casting temperature of the above molten liquid is maintained at 2600°C to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2020°C, and it is kept at this temperature for 120 minutes, then cooled to 1420°C at a rate of 20-30°C / h, and kept at this temperature for 60 minutes, then cooled to 980°C at a rate of 40-50°C / h, and then cooled to 440°C at a rate of 20-30°C / h, and then naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0053] Example 8
[0054] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.968% of aluminum oxide with a particle size of 200-300nm, 112.432% of aluminum oxide with a particle size of 25-50μm, 29.718% of zirconium dioxide with a particle size of 50-100nm, 8.382% of zirconium dioxide with a particle size of 50-100μm, 12.2% of silicon dioxide with a particle size of 100-200nm, 3.1% of niobium pentoxide, 0.9% of soda ash, 0.7% of manganese dioxide and 0.6% of copper oxide;
[0055] The specific process of its preparation method is exactly the same as that of Example 7.
[0056] Example 9
[0057] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 37.8792% of aluminum oxide with a particle size of 200-300nm, 12.5208% of aluminum oxide with a particle size of 25-50μm, 29.5275% of zirconium dioxide with a particle size of 50-100nm, 8.5725% of zirconium dioxide with a particle size of 50-100μm, 12.2% of silicon dioxide with a particle size of 100-200nm, 3.1% of niobium pentoxide, 0.9% of soda ash, 0.7% of manganese dioxide and 0.6% of copper oxide;
[0058] The specific process of its preparation method is the same as that of Example 7.
[0059] Example 10
[0060] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.08% of aluminum oxide with a particle size of 200-300nm, 13.32% of aluminum oxide with a particle size of 25-50μm, 28.575% of zirconium dioxide with a particle size of 50-100nm, 9.525% of zirconium dioxide with a particle size of 50-100μm, 12.2% of silicon dioxide with a particle size of 100-200nm, 3.1% of niobium pentoxide, 0.9% of soda ash, 0.7% of manganese dioxide and 0.6% of copper oxide;
[0061] The specific process of its preparation method is exactly the same as that of Example 7.
[0062] Embodiment 11
[0063] A dense, crack-resistant fused zirconium corundum brick, the raw materials and composition of which are exactly the same as those in Example 5;
[0064] The specific process of the preparation method is partially the same as that of Example 5, except that: (3) in a specially designed product mold, the above-mentioned molten liquid with a casting temperature of 2650°C is cast to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2050°C, and the temperature is reduced to 1370°C at a rate of 20-30°C / h, and then reduced to 1015°C at a rate of 40-50°C / h, and then reduced to 460°C at a rate of 20-30°C / h. After that, it is naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0065] Example 12
[0066] A dense, crack-resistant fused zirconium corundum brick, the raw materials and composition of which are exactly the same as those in Example 9;
[0067] The specific process of the preparation method is partially the same as that of Example 9, except that: (3) in a specially designed product mold, the above-mentioned molten liquid with a casting temperature of 2640°C is cast to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2010°C, and the temperature is reduced to 1390°C at a rate of 20-30°C / h, and then reduced to 990°C at a rate of 40-50°C / h, and then reduced to 450°C at a rate of 20-30°C / h. After that, it is naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0068] Comparative Example 1
[0069] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.974% of aluminum oxide with a particle size of 200-300nm, 11.826% of aluminum oxide with a particle size of 25-50μm, 27% of zirconium dioxide with a particle size of 50-100nm, 9% of zirconium dioxide with a particle size of 50-100μm, 14.2% of silicon dioxide with a particle size of 100-200nm, 3.2% of niobium pentoxide, 1.1% of soda ash, 0.9% of manganese dioxide and 0.8% of copper oxide;
[0070] The specific process of its preparation method is exactly the same as that of Example 5.
[0071] Comparative Example 2
[0072] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 29.89% of aluminum oxide with a particle size of 200-300nm, 12.81% of aluminum oxide with a particle size of 25-50μm, 31.98% of zirconium dioxide with a particle size of 50-100nm, 9.02% of zirconium dioxide with a particle size of 50-100μm, 12% of silicon dioxide with a particle size of 100-200nm, 2.5% of niobium pentoxide, 0.7% of soda ash, 0.6% of manganese dioxide and 0.5% of copper oxide;
[0073] The specific process of its preparation method is exactly the same as that of Example 4.
[0074] Comparative Example 3
[0075] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 29.89% of aluminum oxide with a particle size of 200-300nm, 12.81% of aluminum oxide with a particle size of 25-50μm, 31.59% of zirconium dioxide with a particle size of 50-100nm, 8.91% of zirconium dioxide with a particle size of 50-100μm, 12.7% of silicon dioxide with a particle size of 100-200nm, 2.3% of niobium pentoxide, 0.7% of soda ash, 0.6% of manganese dioxide and 0.5% of copper oxide;
[0076] The specific process of its preparation method is exactly the same as that of Example 4.
[0077] Comparative Example 4
[0078] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 32.85% of aluminum oxide with a particle size of 200-300nm, 10.95% of aluminum oxide with a particle size of 25-50μm, 29.84% of zirconium dioxide with a particle size of 50-100nm, 7.46% of zirconium dioxide with a particle size of 50-100μm, 11.5% of silicon dioxide with a particle size of 100-200nm, 4.6% of niobium pentoxide, 0.8% of soda ash, 1% of manganese dioxide and 1% of copper oxide.
[0079] The specific process of its preparation method is exactly the same as that of Example 6.
[0080] Comparative Example 5
[0081] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 32.85% of aluminum oxide with a particle size of 200-300nm, 10.95% of aluminum oxide with a particle size of 25-50μm, 37.5% of zirconium dioxide with a particle size of 50-100nm, 11.5% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide, 0.8% of soda ash, 1% of manganese dioxide and 1% of copper oxide.
[0082] The specific process of its preparation method is exactly the same as that of Example 6.
[0083] Comparative Example 6
[0084] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 32.85% of aluminum oxide with a particle size of 200-300 nm, 10.95% of aluminum oxide with a particle size of 25-50 μm, 37.5% of zirconium dioxide with a particle size of 50-100 μm, 11.5% of silicon dioxide with a particle size of 100-200 nm, 4.4% of niobium pentoxide, 0.8% of soda ash, 1% of manganese dioxide and 1% of copper oxide;
[0085] The specific process of its preparation method is exactly the same as that of Example 6.
[0086] Comparative Example 7
[0087] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 43.8% of aluminum oxide with a particle size of 200-300nm, 30% of zirconium dioxide with a particle size of 50-100nm, 7.5% of zirconium dioxide with a particle size of 50-100μm, 11.5% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide, 0.8% of soda ash, 1% of manganese dioxide and 1% of copper oxide;
[0088] The specific process of its preparation method is exactly the same as that of Example 6.
[0089] Comparative Example 8
[0090] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 43.8% of aluminum oxide with a particle size of 25 to 50 μm, 30% of zirconium dioxide with a particle size of 50 to 100 nm, 7.5% of zirconium dioxide with a particle size of 50 to 100 μm, 11.5% of silicon dioxide with a particle size of 100 to 200 nm, 4.4% of niobium pentoxide, 0.8% of soda ash, 1% of manganese dioxide and 1% of copper oxide;
[0091] The specific process of its preparation method is exactly the same as that of Example 6.
[0092] Comparative Example 9
[0093] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.08% of aluminum oxide with a particle size of 200-300nm, 13.32% of aluminum oxide with a particle size of 25-50μm, 28.575% of zirconium dioxide with a particle size of 50-100nm, 9.525% of zirconium dioxide with a particle size of 50-100μm, 12.9% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide, 0.9% of soda ash and 0.6% of copper oxide;
[0094] The specific process of its preparation method is exactly the same as that of Example 10.
[0095] Comparative Example 10
[0096] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.08% of aluminum oxide with a particle size of 200-300nm, 13.32% of aluminum oxide with a particle size of 25-50μm, 28.575% of zirconium dioxide with a particle size of 50-100nm, 9.525% of zirconium dioxide with a particle size of 50-100μm, 12.8% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide, 0.9% of soda ash and 0.7% of manganese dioxide;
[0097] The specific process of its preparation method is exactly the same as that of Example 10.
[0098] Comparative Example 11
[0099] A dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 31.08% of alumina with a particle size of 200-300nm, 13.32% of alumina with a particle size of 25-50μm, 28.575% of zirconium dioxide with a particle size of 50-100nm, 9.525% of zirconium dioxide with a particle size of 50-100μm, 13.5% of silicon dioxide with a particle size of 100-200nm, 4.4% of niobium pentoxide and 0.9% of soda ash;
[0100] The specific process of its preparation method is exactly the same as that of Example 10.
[0101] Comparative Example 12
[0102] A dense, crack-resistant fused zirconium corundum brick, the raw materials and composition of which are exactly the same as those in Example 5;
[0103] The specific process of its preparation method is partially the same as that of Example 5, except that: (3) in a specially designed product mold, the above-mentioned molten liquid with a casting temperature of 2640°C is cast to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2010°C, and the temperature is kept for 2 hours, and then the temperature is reduced to 450°C at a rate of 20-40°C / h, and then naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0104] Comparative Example 13
[0105] A dense, crack-resistant fused zirconium corundum brick, the raw materials and composition of which are exactly the same as those in Example 5;
[0106] The specific process of its preparation method is partially the same as that of Example 5, except that: (3) in a specially designed product mold, the above-mentioned molten liquid with a casting temperature of 2640°C is cast to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 2010°C and kept warm for 2 hours. The temperature is then reduced to 450°C at a rate of 40-50°C / h, and then naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0107] Comparative Example 14
[0108] A dense, crack-resistant fused zirconium corundum brick, the raw materials and composition of which are exactly the same as those in Example 5;
[0109] The specific process of its preparation method is partially the same as that of Example 5, except that: (3) in a specially designed product mold, the above-mentioned molten liquid with a casting temperature of 2640°C is cast to form a solid fused brick, which is then annealed and cooled. The annealing starting temperature is 1950°C and kept warm for 2 hours. The temperature is then reduced to 450°C at a rate of 70-80°C / h, and then naturally cooled to obtain a dense, crack-resistant fused zirconium corundum brick.
[0110] Test example: Performance test of dense crack-resistant fused zirconium corundum bricks
[0111] The above-mentioned Examples 1 to 12 and Comparative Examples 1 to 14 were tested according to the Chinese building materials industry standard "Fused-cast zirconium corundum refractory products for glass melting furnaces" (JC493-2001)) and GB / T2997-2015, and the results are shown in Tables 1 and 2.
[0112] Table 1 Test results of Examples 1 to 12
[0113]
[0114] Table 2 Test results of Examples 1 to 12
[0115]
[0116]
[0117] A large number of experiments have shown that, in combination with Table 1 and Table 2, the dense and crack-resistant fused zirconium corundum bricks of the present invention can greatly improve the density of the fused zirconium corundum bricks and reduce the appearance of pores by introducing an appropriate amount of niobium pentoxide into an appropriate amount of alumina, zirconium dioxide and silicon dioxide composition system, and introducing manganese dioxide and copper oxide to synergistically act with niobium pentoxide, significantly reducing the diffusion and mutual penetration of the alkaline glass liquid and the precipitated glass phase, and improving the corrosion resistance; at the same time, in the composition system, alumina and zirconium dioxide interact with each other through a suitable particle size ratio, so that the density of the fused zirconium corundum bricks is greatly improved and the deformation of the glass phase is significantly reduced; in addition, the present invention adopts a suitable annealing method to further improve the dense and crack-resistant fused zirconium corundum bricks with good product quality.
[0118] It can be seen from Tables 1 and 2 that the test results of the embodiments are generally better than those of the comparative examples; compared with Examples 1 to 3, in the alumina of Examples 4 to 7, the mass fraction of alumina with a particle size of 25 to 50 μm accounts for 25 to 30% of the alumina with a particle size of 200 to 300 nm, and in the zirconium dioxide, the mass fraction of zirconium dioxide with a particle size of 50 to 100 μm accounts for 20 to 25% of the zirconium dioxide with a particle size of 50 to 100 nm, making the performance of the fused zirconium corundum brick relatively excellent; further, the proportions of each component of the composition system of Examples 8 to 10 are better than those of Examples 4 to 7, among which Example 9 has the best effect and is the best embodiment of the present invention. The test results of the comparative group and the embodiment group show that the manganese dioxide, copper oxide and niobium pentoxide provided by the present invention, as well as aluminum dioxide with a particle size of 25-50 μm, aluminum dioxide with a particle size of 200-300 nm, zirconium dioxide with a particle size of 50-100 μm and zirconium dioxide with a particle size of 50-100 nm are indispensable components with obvious synergistic effect, which can promote the uniform density of the organizational layer between aluminum oxide, zirconium dioxide and silicon dioxide, greatly reduce the appearance of pores, and significantly improve the density of the fused zirconium corundum brick, which can further delay the generation and expansion of cracks, improve its high temperature resistance, corrosion resistance and thermal shock resistance to avoid electric melting.
[0119] In summary, the fused zirconium corundum brick of the present invention has excellent density and crack resistance, and can significantly extend the service life of the refractory material.
[0120] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0121] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A dense crack-resistant fused zirconium corundum brick, characterized in that: The raw materials include, by mass fraction: 42.7-46.6% aluminum oxide, 36.8-40.5% zirconium dioxide, 11.5-14.2% silicon dioxide, 2.5-4.4% niobium pentoxide, 0.7-1.1% soda ash, 0.6-1% manganese dioxide and 0.5-1% copper oxide; The aluminum dioxide is composed of aluminum dioxide with a particle size of 200 to 300 nm and a particle size of 25 to 50 μm; The zirconium dioxide is composed of zirconium dioxide with a particle size of 50 to 100 nm and a particle size of 50 to 100 μm; The particle size of the silicon dioxide is 100-200 nm.
2. A dense crack-resistant fused zirconium corundum brick according to claim 1, characterized in that: In aluminum dioxide, the mass fraction of aluminum dioxide with a particle size of 25 to 50 μm accounts for 25 to 30% of the mass fraction of aluminum dioxide with a particle size of 200 to 300 nm, and in zirconium dioxide, the mass fraction of zirconium dioxide with a particle size of 50 to 100 μm accounts for 20 to 25% of the mass fraction of zirconium dioxide with a particle size of 50 to 100 nm.
3. A dense crack-resistant fused zirconium corundum brick according to claim 2, characterized in that: The dense crack-resistant fused zirconium corundum brick comprises the following raw materials, calculated by mass fraction: 44.5% alumina, 38.1% zirconium dioxide, 12.2% silicon dioxide, 3.1% niobium pentoxide, 0.9% soda ash, 0.7% manganese dioxide and 0.6% copper oxide.
4. A dense crack-resistant fused zirconium corundum brick according to claim 3, characterized in that: In aluminum dioxide, the mass fraction of aluminum dioxide with a particle size of 25 to 50 μm accounts for 28.2% of the mass fraction of aluminum dioxide with a particle size of 200 to 300 nm; and in zirconium dioxide, the mass fraction of zirconium dioxide with a particle size of 50 to 100 μm accounts for 22.5% of the mass fraction of zirconium dioxide with a particle size of 50 to 100 nm.
5. A method for preparing the dense crack-resistant fused zirconium corundum brick according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) grinding alumina, zirconium dioxide and silicon dioxide to a desired particle size, and then uniformly mixing with soda ash, niobium pentoxide, manganese dioxide and copper oxide to obtain a mixture; (2) pouring the above-mentioned mixed material into an electric arc furnace, melting it into a molten liquid at a temperature of 1890-1910° C., and then continuing to heat it to 2730-2750° C., then keeping it warm and blowing oxygen to remove carbon and oxidize the liquid to obtain a molten liquid; (3) The above molten material is cast in a specially designed product mold, and annealed and cooled in stages at different cooling rates to obtain dense, crack-resistant fused zirconium corundum bricks.
6. The method for preparing a dense crack-resistant fused zirconium corundum brick according to claim 5, characterized in that: In step (2), the time for heat preservation and oxygen blowing treatment is 20 to 25 minutes.
7. The method for preparing a dense crack-resistant fused zirconium corundum brick according to claim 5, characterized in that: In step (3), during casting, the temperature of the molten liquid is between 2600 and 2650°C.
8. The method for preparing a dense crack-resistant fused zirconium corundum brick according to claim 5, characterized in that: In step (3), annealing and cooling are performed in stages at different cooling rates: the annealing starting temperature is 2020-2100° C., first cooled to 1350-1420° C. at a rate of 20-30° C. / h, then cooled to 950-1015° C. at a rate of 40-50° C. / h, and then cooled to 410-460° C. at a rate of 20-30° C. / h, and then naturally cooled.
9. The method for preparing a dense crack-resistant fused zirconium corundum brick according to claim 8, characterized in that: The annealing starting temperature is 2020-2100°C and kept at this temperature for 90-120 minutes, then the temperature is lowered to 1350-1420°C and kept at this temperature for 60-90 minutes.
Citation Information
Patent Citations
Method for producing high-purity and high-density zirconia 3D ceramic shell
CN106810251A
Electric molten AZS brick with high electrical resistivity under high temperature and preparation method thereof
CN107555971A
Zirconia-corundum refractory brick and preparation method thereof
CN108752017A
Fused-cast-alumina-zirconia-silica refractory and glass melting furnace employing it
CN1227203A
High-strength compact zirconia-chromia corundum brick
CN1887788A
Cited By
Alumina corundum brick for superhigh-temperature tunnel kiln crown and preparation method of alumina corundum brick
CN121377739A
Alumina corundum bricks for the arch roof of ultra-high temperature tunnel kilns and their preparation method
CN121377739B